2009
DOI: 10.1007/s11605-009-0806-x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Stem Cell Organoid Transplantation Generates Neomucosa in Dogs

Abstract: Background and Aims Intestinal stem cell organoid transplantation generates functional intestinal neomucosa and has been used therapeutically to improve nutrient absorption and cure bile acid malabsorption in rats. We hypothesized that intestinal organoids can be harvested and transplanted to generate intestinal neomucosa in a large animal model. Materials and Methods In group 1, 2-month old beagles (n=6) underwent autotransplantation of intestinal organoids prepared from a segment of their own ileum. In group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…3,4 Following the description of a novel method for their long-term in vitro culture, 5 there have been reports of successful culture of the various mucosal epithelia of murine stomach, murine colon, human small intestine, both benign and neoplastic human 1 colon, and human Barrett's esophagus. [6][7][8] Previous methods for in vivo implantation relied on initial isolation of stem cell clusters surrounded by neighboring mesenchyme, [9][10][11][12] whereas the current culture techniques appear to have obviated this requirement. 13 In vitro cultured small intestinal units have been variously termed enteroids, spheroids, and organoids by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Following the description of a novel method for their long-term in vitro culture, 5 there have been reports of successful culture of the various mucosal epithelia of murine stomach, murine colon, human small intestine, both benign and neoplastic human 1 colon, and human Barrett's esophagus. [6][7][8] Previous methods for in vivo implantation relied on initial isolation of stem cell clusters surrounded by neighboring mesenchyme, [9][10][11][12] whereas the current culture techniques appear to have obviated this requirement. 13 In vitro cultured small intestinal units have been variously termed enteroids, spheroids, and organoids by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TESI has been demonstrated in rats to reverse clinical malabsorption syndromes [7,9]. Recently, we have been the first to report the successful generation of intestinal neomucosa using organoid transplantation in a large animal model [10]. All described models of intestinal organoid transplantation are limited by a major problem that must be addressed in order to translate their success into a clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the isolation and transplantation of 3Dcultured cells can be used to generate neomucosa in a dog model [43]. However the molecular characterization of the presumed "organoids" was not rigorously.…”
Section: Organoid Disease Modeling and Transplantationmentioning
confidence: 99%